2003
DOI: 10.1021/om020784k
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Trimethylaluminum with Lanthanide Aryloxides:  Adduct and Tetramethylaluminate Formation

Abstract: The reaction of various highly substituted lanthanide(III) and -(II) aryloxide complexes with trimethylaluminum (TMA) was investigated. The solvent-free, π-arene-bridged dimers [Ln(OAr i Pr,H)3]2, derived from the ortho-iPr2-substituted aryloxide ligand OC6H3 i Pr2-2,6, form bis-TMA adduct complexes, Ln(OAr i Pr,H)3(AlMe3)2, for the metal centers yttrium, samarium, and lanthanum. Homoleptic monomeric Ln(OAr)3, featuring a large La center and sterically bulkier ortho-tBu2-substituted aryloxide ligands, affor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 60 publications
3
66
0
Order By: Relevance
“…Cg1, Cg2, Cg3 and Cg4 are the centroids of the C33-C38, C39-C44, C52-C57 and C19-C24 rings, respectively. Occhipinti et al, 2011;GEQMOF, GEQMUL, Fischbach et al, 2006b) Biagini et al, 1994;WAPYIV, WAPYOB, Evans et al, 1993a;WEHHAS, Evans et al, 1993b) Fischbach et al, 2003;MIMPED, Giesbrecht et al, 2002;MOQYOG, Gordon et al, 2002;PETMUX, Fischbach et al, 2006c) Giesbrecht et al, 2002;ROCHOH, Sommerfeldt et al, 2008) Evans et al, 1998). MIMPED is the only La structure among them.…”
Section: Database Surveymentioning
confidence: 99%
“…Cg1, Cg2, Cg3 and Cg4 are the centroids of the C33-C38, C39-C44, C52-C57 and C19-C24 rings, respectively. Occhipinti et al, 2011;GEQMOF, GEQMUL, Fischbach et al, 2006b) Biagini et al, 1994;WAPYIV, WAPYOB, Evans et al, 1993a;WEHHAS, Evans et al, 1993b) Fischbach et al, 2003;MIMPED, Giesbrecht et al, 2002;MOQYOG, Gordon et al, 2002;PETMUX, Fischbach et al, 2006c) Giesbrecht et al, 2002;ROCHOH, Sommerfeldt et al, 2008) Evans et al, 1998). MIMPED is the only La structure among them.…”
Section: Database Surveymentioning
confidence: 99%
“…[9] In addition to strained siloxane bridges [SiOSi ], Brønsted acidic Q 3 functionalities feature reactive surface sites on silica supports that are predominantly available after partial dehydration at elevated temperatures. [3,4] More recently, Gauvin et al reported on the equimolar reaction of www.chemeurj.org 3 ] 2 , due to the Schlenk equilibrium prevailing in solution.…”
Section: The Siloxide Modelmentioning
confidence: 99%
“…[4][5][6] The synthesis of molecular complexes mimicking such surface species is a viable/popular approach to obtain more insight into the nature of a given immobilization scenario. [7] In the meantime, sterically demanding monovalent silanols, such as triphenylsilanol [8] or tris(tert-butoxy)silanol, [9] and multivalent, incompletely condensed oligosilsesquioxanes [10] or calixarenes [11] are routinely employed to assess the local environment of silica-grafted organometallics.…”
Section: Introductionmentioning
confidence: 99%
“…The aluminum cocatalyst was speculated to have an activating effect by either increasing the concentration of active Nd or by increasing the number of active sites per Nd. Anwander et al 3,[22][23][24][25][26] focused on the precise structure of Nd-Al compounds. Elaborated crystal samples were used for X-ray structure determination.…”
Section: Introductionmentioning
confidence: 99%